The Impact of Corporate Governance Mechanisms by the External Auditor for Financial Reporting - جلال حسن, سردار; على احمد, رزكار (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The audit of financial statements is one of the most important control mechanisms that help reduce information asymmetry and protect stakeholders, especially potential shareholders and investors, by providing reasonable assurance that the financial statements prepared by departments are free from material misstatements and intentional errors. External is critical to the quality and quality of financial reporting and the level of confidence by users of accounting information. The concern for the quality of external auditing is one of the issues of corporate governance. It assumes that when corporate governance mechanisms are strong, corporate governance requires a set of relationships between company managers, shareholders and other stakeholders; It provides the structure by which the objectives of the company are set, the means to achieve those objectives, and the monitoring of performance. This indicates that corporate governance is concerned with both the internal aspects of the company, such as the internal control system, and external control. Corporate governance has become a means to strengthen the country's economy and evidence of fair and transparent policies and rules to protect investors and dealers. The research was analyzed by statisticians using SPSS software and a questionnaire was distributed to a group of sample companies.